Effect of Nurses’ Motivation on Quality of Nursing Services in Imelda General Hospital, Medan - Delfi Gunawaty; Surya Utama; Juanita Juanita (International Journal of Nursing and Health Services (IJNHS), 2020)
Services in hospitals are supported by human resources that are dominated by nurses. Motivation is an impetus that arises in the self to take action to achieve goals. Nurses' motivation to work is salary, promotion, training, recognition, supervision, work team, work comfort, work environment and responsibilities. The quality of nursing services as an indicator of the quality of health services is one of the determining factors in the image of health service institutions in the eyes of the community, whether the services provided are satisfactory or not. This type of research is a survey with an explanatory research type, which aims to explain the influence of motivation (salary, promotion of positions, training, recognition, supervision, work team, work comfort, work environment and responsibility) on the utilization of the quality of nursing services at the Imelda General Hospital, Medan . The study was conducted at Imelda General Hospital, Medan. The population in this study were all implementing nurses, amounting to 180 people. The number of samples in this study were 64 people obtained by simple random sampling technique. Analysis of the data used is multiple linear regression. The results showed that the motivation of nurses at Imelda General Hospital was moderate motivation (84%). The quality of nursing services at Imelda General Hospital is of poor quality (55%). Variables that influence the quality of nursing services are salary, training, work teams and supervision. The contribution of the five variables to the quality of nursing services was 77%. Of the five variables the strongest influence on the quality of nursing services is training (B = 3,536). It is recommended to the Imelda General Hospital to formulate policies and regulations regarding the implementation of basic education and training that must be owned by a nurse, prepare routine internal training programs, provide opportunities for nurses to continue their education to a higher education level, conduct regular nursing audits which includes evaluation of nursing care documentation, completeness of patient files, assessment of nursing actions in order to improve professionalism and quality of nursing services.